Paeoniflorin mitigates MMP-12 inflammation in silicosis via Yang-Yin-Qing-Fei Decoction in murine models - Li, Tian; Mao, Na; Xie, Zihao; Wang, Jianing; Jin, Fuyu; Li, Yaqian; Liu, Shupeng; Cai, Wenchen; Gao, Xuemin; Wei, Zhongqiu; Yang, Fang; Xu, Hong; et al. (Phytomedicine (Stuttgart), 2024)
Silicosis presents a significant clinical challenges and economic burdens, with Traditional Chinese Medicine (TCM) emerging as a potential therapeutic avenue. However, the precise effects and mechanisms of TCM in treating silicosis remain uncertain and subject to debate. The study aims to elucidate the therapeutic role and mechanisms of the Yang-Yin-Qing-Fei Decoction (YYQFD) and its key component, paeoniflorin, in silicosis using a murine model. Silicotic mice were treated with YYQFD, pirfenidone (PFD), or paeoniflorin. RAW264.7 cells and mouse lung fibroblasts (MLF) were stimulated with silica, matrix metalloproteinase-12 (MMP-12), or TGF-β1, followed by treatment with paeoniflorin, PFD, or relevant inhibitors. YYQFD constituents were characterized using High-Performance Liquid Chromatography (HPLC). Lung fibrosis severity was assessed via histopathological examination, micro-CT imaging, lung functions, and Western blot analysis. Transcriptome sequencing and bioinformatics analysis were employed to delineate the gene expression profile and target genes modulated by YYQFD in silicosis. Treatment with YYQFD ameliorated silica-induced lung fibrosis. Transcriptome sequencing identified MMP-12 as a potential common target of YYQFD and PFD. Additionally, a potential pro-inflammatory role of MMP-12, regulated by silica-induced TLR4 signaling pathways, was revealed. Paeoniflorin, one of the most distinctive compounds in YYQFD, attenuated silica-induced MMP-12 increase and its derived inflammatory factors in macrophages through a direct binding effect. Notably, paeoniflorin treatment exerted anti-fibrotic effects by inhibiting MMP-12-derived inflammatory factors and TGF-β1-induced myofibroblast differentiation in silica-exposed mice. This study underscores paeoniflorin as one of the most principal bioactive compounds in YYQFD, highlighting its capacity to attenuate lung inflammation driven by macrophage-derived MMP-12 and reduce lung fibrosis both in vivo and in vitro. [Display omitted]